Mechanical properties of structural materials and methods of their determination : Monograph - Moshchenok, Vasyl; Stoev, Peter; Lalazarova, Natalia (LAMBERT Academic Publishing, 2024)
The main objective of this book is to describe the mechanical properties of materials and methods of their study. The textbook is intended for researchers, engineers, as well as for students, bachelors, masters, and postgraduate students of technical educational institutions. Today, great attention is paid to improving the quality of structural materials by improving their performance properties, which determine the behavior of materials during mechanical and thermal processing and in service. To evaluate the performance properties, various tests are carried out that simulate, to varying degrees, a variety of operating and processing conditions. The objective of this manual is to help you master various methods of testing structural materials, to familiarize yourself with the procedure and basic research equipment, to gain skills in analyzing experimental results and calculating the measured characteristics.
Keywords: mechanical engineering; production technology